2022
DOI: 10.3389/fped.2022.956920
|View full text |Cite
|
Sign up to set email alerts
|

Teaching fiberoptic-assisted tracheoscopy in very low birth weight infants: A randomized controlled simulator study

Abstract: ObjectiveWe developed a fiberoptic-assisted tracheoscopy (FAST) method to avoid direct laryngoscopy during surfactant replacement therapy and compared two training approaches on a very low birth weight (VLBW) infant simulator.DesignThis prospective randomized controlled study was conducted at the Department of Neonatology and Pediatric Intensive Care Medicine of the University Medical Center Hamburg-Eppendorf, Germany.ParticipantsWe recruited physicians, trainees, students, and nurses without prior experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Given the limitations of the LBL method, it is imperative that we seek innovative teaching approaches. It has been shown that the new methods significantly elevate the caliber of nursing education by promoting active engagement and critical analysis, and also positively impact patient care [33][34][35][36]. Our study indicates that the CDIO model group participants outperformed the control group in both theoretical knowledge assessment and application capability evaluation, with a statistically significant difference after training (F = 12.116, p = 0.001 for theoretical knowledge; F = 23.681, p < 0.001 for application capability; Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…Given the limitations of the LBL method, it is imperative that we seek innovative teaching approaches. It has been shown that the new methods significantly elevate the caliber of nursing education by promoting active engagement and critical analysis, and also positively impact patient care [33][34][35][36]. Our study indicates that the CDIO model group participants outperformed the control group in both theoretical knowledge assessment and application capability evaluation, with a statistically significant difference after training (F = 12.116, p = 0.001 for theoretical knowledge; F = 23.681, p < 0.001 for application capability; Table S2).…”
Section: Discussionmentioning
confidence: 99%